Empowering Women in the Digital Age: Legal Strategies for Gender Equality Inspired by Kartini’s Vision - Nurmayani, Ika Dewi (Law and Judicial Review, 2025)
Objective: The objective of this study is to explore women's empowerment in the digital age in Indonesia, focusing on the challenges of gender-based digital inequality and the legal strategies needed to address these issues, as inspired by Kartini's vision. The research aims to assess the role of digital technology in empowering women, while examining legal policies related to gender equality and digital rights. Research Design & Methods: This research uses a qualitative descriptive methodology, which focuses on an in-depth and detailed analysis of women's empowerment in the digital age through a legal lens. Data was collected from primary sources (e.g., legal documents, interviews with legal experts, policymakers, and activists) and secondary sources (e.g., academic literature, government reports, and online publications) to examine current legal policies, digital technology, and gender equality issues in Indonesia. Findings: The study found that digital technologies provide opportunities for women to fight for their rights and participate in social movements, although gender-based digital inequality and online violence remain significant obstacles, requiring further development of legal policies to empower women and provide protection against digital discrimination. Implications & Recommendations: The study recommends that the Indonesian government strengthen policies to combat online violence and digital discrimination and support digital literacy for women, legal institutions increase enforcement of gender equality in digital spaces and provide legal protection, NGOs raise awareness about digital violence, and women are encouraged to be more active in digital spaces by understanding the risks and protections related to digital violence. Contribution & Value Added: This study contributes to the literature on women's empowerment in the digital age by exploring the relationship between gender equality, legal strategies, and digital technologies, and provides insights into how legal frameworks can address the challenges women face in the digital space, while emphasizing Kartini's vision and offering recommendations for legal reform and digital literacy to support gender equality in Indonesia and other developing countries.